Enhancing the Skills of Mate Jaklou Pokmaswas in Raja Ampat Through Literacy Training - Dayu Rifanto; Jajat S Ardiwinata; Joni Rahmat Pramudia; Hans Agung Pasak; Tri Kurnia Goram; Zakarias Magari (Jurnal Pemberdayaan Masyarakat, 2025)
This study evaluates the effectiveness of literacy training for Pokmaswas in the Raja Ampat region, especially in North and East Misool, using a pre-experimental method with a one-group pretest-posttest design. The main focus is improving literacy and conservation awareness among Pokmaswas members and teachers. Quantitative data were collected through pre-test and post-test, while qualitative data were obtained through in-depth interviews. The results showed a significant increase in understanding among participants, with the average score rising from 30 to 48.94 at Pos Kasim and from 34.16 to 54.16 at Pos Fol Pulau in Folley Island. Most participants achieved "Satisfactory" and "Very Satisfactory" ratings, although some remained in the "Unsatisfactory" and "Very Unsatisfactory" categories, indicating a need for a more tailored approach and further guidance. The activities also raised awareness of the sustainability of natural resources, integrating traditional practices such as Sasi and Pokmaswas activities to educate the community. However, there are challenges in ensuring equal access to literacy in remote areas, which require ongoing support from various parties to enhance the program's effectiveness and reach. This study emphasizes the importance of literacy as a key to supporting conservation and preserving local knowledge through education, particularly with children's books that are contextually relevant.